Microplastics influence the functional responses of a tropical estuarine calanoid Pseudodiaptomus annandalei - Sharma, Jaigopal; Rai, Malayaj; Guino-o, Robert S. (Frontiers in Ecology and Evolution, 2024)
Being chemically inert and morphologically similar (<5 mm in size) to the natural prey of copepods, microplastics (MPs) affect them through entanglement, ingestion, and interference with their natural prey selection. The effects of external factors, such as MP, can be observed in the form of alterations in the functional and numerical responses of copepods. Functional response is explained as the relationship between the intake rate of a consumer and the amount of food available in a particular ecotope. Considered three types of functional response: (i) with increasing food density, when intake rate increases linearly until asymptote, called Type-I functional response; (ii) when the proportion of prey ingested by the consumer decreases monotonically with prey density, considered as a Type-II functional response; and (iii) when ingestion rate and food density show a sigmoid relationship, is considered as Type-III functional response. In the present study, we attempted to elucidate the effects of MP on the functional responses of brackish water, demersal, calanoid copepod, Pseudodiaptomus annandalei, feeding on the rotifer Brachionus rotundiformis, and the ciliate Frontonia microstoma. The ability of P. annandalei to survive environmental fluctuations and its nutritional value make it an ecologically important organism in estuarine ecosystems. The experiment for estimation of functional response included four setups with adult and copepodite stages of P. annandalei, each with six replicates at six different prey densities, in the presence and absence of MP particles. Without MPs, P. annandalei showed a typical Type-II functional response, where the proportion of prey consumed significantly declined with increasing prey density. In the MP-applied medium, the proportion of prey consumed did not exhibit a significant relationship with the initial prey density. The number of ciliates and rotifers ingested by copepodites and adults was significantly lower in MP-contaminated medium than in prey either monospecific or in combination with microalgae. Because of the comparable size of MP to the prey species and unspecialized feeding of P. annandalei in natural waters, we hypothesized reduced predation rates as a result of pseudo-satiation resulting from MP ingestion leading to malnutrition and MP storage in copepod biomass.